ANALISIS KINERJA SIMPANG TIGA BERSINYAL ANALISIS KINERJA SIMPANG TIGA BERSINYAL MENGGUNAKAN METODE PKJI 2014 (STUDI KASUS SIMPANG TIGA PASAR WARUNGASEM)MENGGUNAKAN METODE PKJI 2014 (STUDI KASUS SIMPANG TIGA PASAR WARUNGASEM) - Muhammad Rezki Ian; Jamal; Muhammad Afifudin (JERA : Journal of Engineering Research and Application, 2024)
Warungasem Market is one of the intersections that has a high traffic volume during rush hour because this intersection is located in a commercial area, namely the Warungasem traditional market which is the center of trading activities in Warungasem District. This market is also located on an alternative road that connects Batang Regency with Pekalongan Regency. . This causes high traffic volumes on the roads connected to the market area. The aim of this research is to determine the characteristics and performance of intersections in the Warungasem market. This research uses the 2014 PKJI reference in conducting research. Peak hour traffic volume is 1233.35 cur/hour. The traffic flow on the North arm is 408.7 cur/hour, on the East arm 365.65 cur/hour, and on the West arm 459 cur/hour. The capacity of the North arm is 454 cur/hour, the East arm is 567 cur/hour, and the West arm is 456 cur/hour. The degree of saturation for the North arm is 0.901, the East arm is 0.645, and the West arm is 1.01. The length of the queue for the North arm is 60 m, the East arm is 35 m, and the West arm is 115 m. The average delay value at the Warungasem Market intersection is 71.8 seconds/cur. The level of service shows that it is in class F. This shows that the road capacity is small and not commensurate with the volume of vehicles during peak hours, namely 06.30-07.30 WIB, especially on the west arm, causing an increase in the degree of saturation, long queues and delays.